1997
DOI: 10.1161/01.hyp.30.6.1499
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Nitric Oxide and N -Methyl- d -Aspartate Receptors in the Nucleus Tractus Solitarii of Rats

Abstract: Nitric oxide (NO) is an endogenously synthesized effector molecule that acts as a neurotransmitter with novel properties in both the central and peripheral nervous systems. We previously reported that NO was involved in central cardiovascular regulation and modulated the baroreflex in the nucleus tractus solitarii (NTS) of rats. The aim of the present study was to determine whether NO and excitatory amino acids reciprocally release each other in the NTS. In normotensive Sprague-Dawley rats, intra-NTS microinje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
47
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 26 publications
3
47
0
1
Order By: Relevance
“…14 We have recently demonstrated that NO can cause regulation of blood pressure in the central nervous system. 2,15,16 These data strongly suggest that the insulin-PI3K-Akt-NOS signaling pathway in the NTS is involved in central cardiovascular regulation.In the present study, we investigated the cardiovascular effects of insulin in the NTS of Wistar-Kyoto (WKY) rats of different ages. Our results showed that insulin and its downstream molecules, such as PI3K, Akt, and NOS, are involved in the regulation of central cardiovascular effects in the NTS of WKY rats.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…14 We have recently demonstrated that NO can cause regulation of blood pressure in the central nervous system. 2,15,16 These data strongly suggest that the insulin-PI3K-Akt-NOS signaling pathway in the NTS is involved in central cardiovascular regulation.In the present study, we investigated the cardiovascular effects of insulin in the NTS of Wistar-Kyoto (WKY) rats of different ages. Our results showed that insulin and its downstream molecules, such as PI3K, Akt, and NOS, are involved in the regulation of central cardiovascular effects in the NTS of WKY rats.…”
mentioning
confidence: 78%
“…14 We have recently demonstrated that NO can cause regulation of blood pressure in the central nervous system. 2,15,16 These data strongly suggest that the insulin-PI3K-Akt-NOS signaling pathway in the NTS is involved in central cardiovascular regulation.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…14 Furthermore, it has been reported that perfusion of adenosine through a microdialysis probe can increase the release of glutamate in the NTS. 11 17,19,20 CO is a second simple diatomic gas molecule that shares some physicochemical properties of NO. These studies suggest that CO may be a neurotransmitter in the nervous system.…”
mentioning
confidence: 99%